2017
DOI: 10.1002/jmv.24722
|View full text |Cite
|
Sign up to set email alerts
|

Oropouche virus is detected in peripheral blood leukocytes from patients

Abstract: Oropouche virus (OROV) is a frequent cause of arboviral febrile disease in the Amazon. The present report describes studies done in two patients, one of them; the first OROV human case acquired outside of the Amazon, which have revealed for the first time the presence of OROV in peripheral blood leukocytes. This novel finding raises important issues regarding pathogenesis of human infections and may offer a new tool, for the rapid diagnosis of this neglected infection. J. Med. Virol. 89:1108-1111, 2017. © 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 15 publications
2
25
0
3
Order By: Relevance
“…While these were residual samples that may have been degraded by freeze/thaw cycles, our findings are consistent with prior results; JCV has never been isolated from human samples, and one study demonstrated no detectable viremia in experimentally infected rhesus macaques, despite seroconversion [34]. In general for orthobunyaviruses, it has been challenging to grow virus [35] or detect viral RNA in human samples; the few exceptions to this have included the detection of RNA from LACV in brain tissue [36], Oropouche virus in leukocytes [37], and Cache Valley virus in the CSF of an immunocompromised patient [38]. Overall, our results suggest that viral RNA detection techniques are unlikely to be useful for routine JCV diagnostics, likely because of lowlevel or short viremia.…”
Section: Discussionsupporting
confidence: 89%
“…While these were residual samples that may have been degraded by freeze/thaw cycles, our findings are consistent with prior results; JCV has never been isolated from human samples, and one study demonstrated no detectable viremia in experimentally infected rhesus macaques, despite seroconversion [34]. In general for orthobunyaviruses, it has been challenging to grow virus [35] or detect viral RNA in human samples; the few exceptions to this have included the detection of RNA from LACV in brain tissue [36], Oropouche virus in leukocytes [37], and Cache Valley virus in the CSF of an immunocompromised patient [38]. Overall, our results suggest that viral RNA detection techniques are unlikely to be useful for routine JCV diagnostics, likely because of lowlevel or short viremia.…”
Section: Discussionsupporting
confidence: 89%
“…OROV is also distributed to areas where hematophagous mosquito species Culex quinquefasciatus , Coquillettidia venezuelensis , and Aedes (Ochlerotatus) serratus can breed and may be naturally infected by the virus [ 1 , 32 , 33 ]. It is well documented that, in 1960, OROV was isolated from mosquito species Cq.…”
Section: Arthropod Vectorsmentioning
confidence: 99%
“…serratus , Cx. quinquefasciatus and midges of the genus Culicoides have been reported to be likely vectors in the sylvatic cycle as indicated by epidemiological and laboratory based evidence [ 4 , 33 , 41 , 43 , 44 ].…”
Section: Transmission Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenômenos hemorrágicos (petequias, epistaxe e sangramento gengival) na doença por OROV foram relatados em um surto ocorrido em Manaus (MOURÃÃO et al, 2009). O vírus encontra-se presente e se dissemina em leucócitos do sangue periférico (DE SOUZA LUNA et al, 2017). Embora a maioria dos pacientes se recupere dentro de 2 a 3 semanas sem seqüelas de longo prazo (PINHEIRO et al, 1981a), recidivas são comuns (PINHEIRO et al, 1981a).…”
Section: Eia-iccunclassified